Low‐Temperature Relaxations Associated with Mixed‐Valent Structure in Sr2TiMnO6. Issue 2 (2nd November 2012) - Sun, Xiaohong; Wang, Chunchang; Wang, Guojing; Lei, Changmei; Teng Li,; Liu, Lina; Chen, X. M.
<x xml:space="preserve">Abstract</x> The dielectric properties of Sr2TiMnO6 ceramic samples were investigated as functions of temperature (100 K ≤ T ≤ 320 K) and frequency (100 Hz ≤ f ≤ 10 MHz). Two thermally activated dielectric relaxations were observed. The sample was confirmed to possess multivalent states of Mn and Ti ions and the coexistence of electron holes and electrons. Our results revealed that both relaxations are bulk effect related to localized carriers hopping inside grains. It was suggested that the low‐temperature relaxation (LTR) can be related to dipolar effect due to electron holes, and the high‐temperature relaxation (HTR) was associated with the electrons hopping between Ti3+ and Ti4+ ions.